A Transcription Factor SlNAC4 Gene of Suaeda liaotungensis Enhances Salt and Drought Tolerance through Regulating ABA Synthesis - Jiahui Liu; Hongfei Wang; Mingxing Su; Qianqian Li; Honglin Xu; Jieqiong Song; Changping Li; Qiuli Li (Plants, 2023)
The NAC (NAM, ATAF1/2 and CUC2) transcription factors are ubiquitously distributed in plants and play critical roles in the construction of plant organs and abiotic stress response. In this study, we described the cloning of a Suaeda liaotungensis K. NAC transcription factor gene SlNAC4, which contained 1450 bp, coding a 331 amino acid. We found that SlNAC4 was highly expressed in stems of S. liaotungensis, and the expression of SlNAC4 was considerably up-regulated after salt, drought, and ABA treatments. Transcription analysis and subcellular localization demonstrated that the SlNAC4 protein was located both in the nucleus and cytoplasm, and contained a C-terminal transcriptional activator. The SlNAC4 overexpression Arabidopsis lines significantly enhanced the tolerance to salt and drought treatment and displayed obviously increased activity of antioxidant enzymes under salt and drought stress. Additionally, transgenic plants overexpressing SlNAC4 had a significantly higher level of physiological indices. Interestingly, SlNAC4 promoted the expression of ABA metabolism-related genes including AtABA1, AtABA3, AtNCED3, AtAAO3, but inhibited the expression of AtCYP707A3 in overexpression lines. Using a yeast one-hybrid (Y1H) assay, we identified that the SlNAC4 transcription factor could bind to the promoters of those ABA metabolism-related genes. These results indicate that overexpression of SlNAC4 in plants enhances the tolerance to salt and drought stress by regulating ABA metabolism.